Virtual reality tools in teaching gross anatomy to sports science undergraduated student: a pilot study - Papa, Veronica; Saracco, Alberto; Vaccarezza, Mauro (EDIZIONI IDELSON-GNOCCHI, 2020)
Medical and health science students need to acquire many skills and theoretical knowledge to become competent practitioners. Anatomy, in particular, can be indeed defined as one of the cornerstones of health education. Nowadays, there is much debate about suitable methods of delivering anatomical knowledge. In response to technological advancements, a wide range of interactive tools have been developed and to enhance students’ learning outcomes. Some of the advantages of 3D anatomical models compared to the standards teaching modules include the enhanced spatial understanding of the inter-relationships between different body structures. This study examined whether or not students’ learning outcomes are influenced both by the addition of three-dimensional and digital teaching tools in conjunction with the standard anatomical education based on a traditional lecture learning format. Our results showed that the use of 3D software improves the motivation of students to learn anatomy as well as promoting active learning and transfer of previously acquired knowledge to practical, relevant subjects. Moreover, most students found that they enjoyed learning anatomy using 3D muscle premium software, and therefore, the use of 3D software improves and facilitates learning compared to frontal lessons or 2D atlas use.